A scoping review of health system guidelines for pharmacist responsibilities when dispensing opioids - William Manning Olsen; Chris Freeman; Adeleke Adewumi; Adam La Caze (Elsevier, 2023)
Introduction: Prescription opioid use and evidence of the harm caused by these medicines has increased over the past 20-30 years. Despite a number of system level interventions, the opioid crisis has not yet resolved in Australia or globally. Pharmacists are increasingly required to take a proactive, clinical role to fulfil their responsibility for patient outcomes relating to both medication efficacy and safety. Aim: To evaluate the current health system guidelines available to pharmacists dispensing opioids and to examine the implications of this guidance on pharmacist responsibility. Methods: A scoping review was conducted by searching in CINAHL, MEDLINE, Embase, PubMed and Web of Science, in addition to the grey literature and referral from topic experts to collate a list of current health system guidelines relevant to pharmacists dispensing opioids. These guidelines were then examined through thematic analysis and the use of the "Appraisal of Guidelines Research & Evaluation-Health Systems" tool (AGREE-HS). Results: Ten health system guidelines were identified in the search. Identified guidelines were published in Australia, the United States, and the United Kingdom. Health system guidelines analysed in this study most commonly provide general practice statements that are not specific to opioid medicines. Current guidelines frequently recommend risk assessment, but less commonly provide implementable risk mitigation advice. Additionally, guidelines are of poor overall quality when analysed through metrics relating to their development and implementation. Conclusion: There are gaps in current health system guidelines which contribute to perceived barriers in pharmacy practice. Current health system guidance does not provide a clear account of the responsibilities of pharmacists when dispensing opioids. This study provides an argument for the development of implementable health system guidelines that support pharmacists in taking direct responsibility for patient outcomes when dispensing opioid medicines.